2019
DOI: 10.1016/j.dcn.2019.100631
|View full text |Cite
|
Sign up to set email alerts
|

Building blocks of joint attention: Early sensitivity to having one’s own gaze followed

Abstract: Detecting when one’s own gaze has been followed is a critical component of joint attention, but little is known about its development. To address this issue, we used electroencephalography (EEG) to record infant neural responses at 6.5 and 9.5 months during observation of an adult either turning to look at the same object as the infant (congruent actor), or turning to look at a different object (incongruent actor). We also used a preferential looking paradigm to investigate whether infants would demonstrate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 116 publications
4
25
1
1
Order By: Relevance
“…This assertion stems from numerous observations. First, research suggests that gaze processing mechanisms appear to contribute to differences in the development of face detection and face processing (25,(136)(137)(138). Indeed, the early cortical face processing indicated by N-170 ERP data may be mediated by eye region processing (136).…”
Section: Social Motivation and The Bi-directional Nature Of Social Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion stems from numerous observations. First, research suggests that gaze processing mechanisms appear to contribute to differences in the development of face detection and face processing (25,(136)(137)(138). Indeed, the early cortical face processing indicated by N-170 ERP data may be mediated by eye region processing (136).…”
Section: Social Motivation and The Bi-directional Nature Of Social Attentionmentioning
confidence: 99%
“…The latter assesses responses to gaze shifts and direction of attention of another person. It also assesses behaviors involving monitoring and leading the gaze and attention of other people to initiate social attention coordination [e.g., (22)(23)(24)(25)]. In this paradigm, gaze following behaviors are referred to as responding to joint attention (RJA) and gaze leading as initiating joint attention [IJA, (26)].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested this modulation was consistent with joint attention’s association with social coordination, mutual attention, and attention mirroring. More recently, an infant EEG study looked specifically at oscillations when infant joint-attention initiation was reciprocated with a congruent gaze shift to an object and found greater α band suppression for congruent gaze shift responses than incongruent ( Rayson, Bonaiuto, Ferrari, Chakrabarti, & Murray, 2019 ). This is evidence that infants as young as 6.5 to 9.5 months old detect whether their gaze has been followed.…”
Section: Electrophysiological Correlates Of Dynamic Joint Gaze States: the Anterior Directing Attention Negativity N330 P3 And Oscillatormentioning
confidence: 99%
“…These outcomes number seven compared with the two (empathizing and theory of mind) included in Baron-Cohen’s (2005) influential model. Our model is also informed by more recent advances that have occurred since the formulation of these previous models, for example, from EEG research (e.g., Lachat et al, 2012 ; Rayson et al, 2019 ), imaging studies (e.g., Cavallo et al, 2015 ; Koike et al, 2016 ), and behavioral studies (e.g., Stephenson et al, 2018 ).…”
Section: A Shared-attention System and Associated Neural Mechanismsmentioning
confidence: 99%
“…One used EEG to record infant neural responses to an adult either turning to look at the same object as the infant (congruent actor) or turning to look at a different object (incongruent actor). Neural responses (alpha desynchronisation) was greater for the congruent actor 83 (see also 84 ). The second study recorded dual EEG during naturalistic child-parent play, and found that, when a parent responded contingently to an infant-led attention shift towards a new play object, the infant showed increased alpha desynchronisation, along with increased attention to that object 85 .…”
Section: Contingent Responsivenessmentioning
confidence: 93%